Relationship between acute stress and clinical performance in medical students: a pilot simulation study. (2nd March 2018) - Russ, Stephanie J; Morrison, Ian; Bell, Cheryl; Morse, Jeremy Charles; Mackenzie, Rhoda Katharine; Johnston, Marie K
Abstract : Background: Acute stress has been linked to impaired clinical performance in healthcare settings. However, few studies have measured experienced stress and performance simultaneously using robust measures in controlled experimental conditions, which limits the strength of their findings. Aim: In the current study we examined the relationship between acute stress and clinical performance in second-year medical students undertaking a simulated ECG scenario. To explore this relationship in greater depth we manipulated two variables (clinical urgency and cognitive load), and also examined the impact of trait anxiety and task self-efficacy. Methods: Second-year medical students were asked to conduct a 12-lead ECG on a simulated patient. Students were randomly assigned to one of four experimental conditions according to clinical urgency (high/low) and cognitive load (high/low), which were manipulated during a handover prior to the ECG. As part of the scenario they were asked to describe the ECG trace to a senior doctor over the phone and to conduct a drug calculation. They then received a performance debrief. Psychological stress and physiological stress were captured (via self-report and heart rate, respectively) and various aspects of performance were observed, including technical competence, quality of communication, work rate and compliance with patient safety checks. Trait anxiety and task self-efficacy were also captured via self-report. Results: Fifty students participated. While there was little impact of experimental condition on stress or performance, there was a significant relationship between stress and performance for the group as a whole. Technical competence was poorer for those reporting higher levels of psychological stress prior to and following the procedure. Neither trait anxiety nor task self-efficacy mediated this relationship. Conclusions: This study has provided evidence for a link between acute stress and impaired technical performance in medical students completing a simulated clinical scenario using real-time measures. The implications for patient safety and medical education are discussed.